ANALISIS PENGUNGKAPAN TATA KELOLA BANK SYARIAH DI INDONESIA - Cahyo Luthfi Adiono; Mahfud Sholihin (Jurnal Keuangan dan Perbankan, 2014)
This research aimed to analyze the disclosure level of corporate governance on annual report of BUS (SyariahCommercial Banks) in Indonesia in 2010-2012 with indicator stated in Indonesia Bank Rules number 11/33/PBI/2009. Besides, this research also analyzed the growth of the disclosure level. To reach the aim, thisresearch used content analysis method. The result of research showed that Syariah Mandiri Bank, BCA SyariahBank, and Muamalat Bank had the highest disclosure value while Bukopin Syariah Bank had the highestgrowth average. However, only four BUS had disclosure value above 70 percent and four BUS had growthrank above 5 percent per year. It showed that during 3 year-period the disclosure level of BUS corporategovernance in annual report was not high and it had not had a meaningful growth.